(untitled) (Journal of actual problems of jurisprudence, 2025)
With the adoption of the Administrative Procedural Procedure Code of the Republic of Kazakhstan, changes have been made in the internal administrative procedures of state bodies, allowing to determine the specific procedure for considering citizens’ appeals in state bodies, which contributes to more effective protection of citizens’ interests, and on the part of administrative bodies and officials - to increase the level of public confidence in the state. At the same time, the authors consider it necessary to finalize the collective appeal procedure, eliminate existing shortcomings in the development of legal norms in ensuring legal regulation of the collective form of filing an appeal, protection of citizens’ rights and freedoms, and their legitimate interests. In the article, the authors analyze the relationship between the terms «person», «citizen», «personality» and their legal status. In the basic terminology of the APPC, it is proposed to give a comprehensive scientific and theoretical definition of the concepts of «administrative process» and «administrative legal proceedings». The study analyzes the issues of administrative procedure and administrative-procedural relations. The right to appeal is one of the most effective ways to eliminate violations, one of the tools for the prevention of offenses, and the protection of human and civil rights and legitimate interests. At the present stage, the specifics of administrative procedure and procedural legislation lie in the fact that for our society, for the time being, it is mostly clear only to specialists, and there is a need to increase the effectiveness of the use of new terms and institutions. It is proposed to improve the norms governing the forms of appeal provided for by the norms of the APPC, that is, the forms of submission, application, complaint, petition, as well as the legislative norms for handing over an administrative act to participants in an administrative process, the forms of filing an appeal in individual and collective forms. Keywords: an individual, a legal entity, an administrative procedure, an administrative body, an application, a complaint, an appeal, an administrative court, an administrative act.